Perbandingan Efektivitas Metode SAW dan AHP dalam Seleksi Penerima Beasiswa di LIPIA Jakarta - Clarita, Anggita Risqi Nur; Fadhillah, Faizah Via; Nurhaliza, Zahra; Fatchan, Muhamad; Anshor, Abdul Halim (Jurnal Ilmiah SINUS, 2025)
This research discusses the application of SAW and AHP methods in the selection process of scholarship recipients at LIPIA Jakarta. Given the complexity of assessing potential recipients, both methods are evaluated to determine which one provides the most accurate and efficient results. SAW and AHP methods are used to process the assessment of several criteria, such as Arabic Written Test, Arabic Oral Test, Diploma Score, Memorization and Good Behavior which have been given weights and scales according to their importance. The main objective of this research is to compare the effectiveness of the two methods in determining scholarship recipients who meet the criteria at LIPIA. The results of this comparison are expected to provide recommendations regarding the most suitable method to improve objectivity, accuracy, and efficiency in scholarship selection.